The Regulation of Suspended Sentence in the Criminal Code of 1968 - Kostadinova, Ralitza (Research Papers, 2020)
This report deals with the institute of suspended sentence and the changes in its treatment brought by the Criminal code enacted in 1968. Consideration is given to the legal requirement placing the possibility to achieve the goals of general and special deterrence as a prerequisite for the application of the institute. The regulations of probation period in previous Criminal laws are put in comparison. Special attention is given to the educative measures introduced by the Code in 1968 as an element of the probation. Two different approaches to the legal treatment of the suspended sentence are outlined - one applicable to juvenile offenders and the other dependent on the crime committed and the possibility to enforce the suspended sentence.
Keywords: Criminal law; Suspended sentence; Probation period; Educative measures; Punishment